The Influence of Transformational Leadership Style, Employee Commitment and Performance on Work Productivity (Case Study at PT. JAMKRINDO) - Rowi, Muchlas (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Jamkrindo is a state-owned enterprise (BUMN) which serves as a means of financing for micro and small and medium industries, to be able to provide good service, it must be supported by good quality human resources, the quality of human resources, especially employees, of course must be sourced from leaders who can provide good examples to their subordinates, therefore in this study the perception of respondents who are leaders of branches, regions and service units is measured through transformational leadership variables, work commitment, employee performance and work productivity, this study uses the SEM method by distributing questionnaires to a sample of 303 respondents using a sampling technique, namely purposive sampling and a margin of error of 5%, and the results obtained are transformational leadership has an influence on work commitment, and also affects performance employees, the next result is the influence of work commitment on employee performance and employee performance has a significant positive effect on work productivity variables. Keywords: Transformational Leadership, Work Commitment, Employee Performance, Work Productivity